Report of the Workshop on Sustainable Rural Telecentres in Africa - Koda Traoré, A.; Crul, Ruud (Technical Centre for Agricultural and Rural Cooperation, 2008)
This workshop aims to contribute to the identification of key factors of success for sustainable rural Telecentres in Africa.